Вариабельность сердечного ритма при хронической сердечной недостаточности (литературный обзор) - А. М. Алиева; Е. З. Голухова; Т. В. Пинчук (Архивъ внутренней медицины)
A large number of studies have produced a lot of evidence that there is a connection between the state of the autonomic regulation of heart rate and mortality from cardio-vascular diseases. To the present time enough experience in the study of heart rate variability in patients with various cardiovascular, endocrine, neurological and other disorders. This review of the literature reveals the great clinical importance of the study of heart rate variability in patients with chronic heart failure in the assessment of autonomic tone and its components, as well as the prediction of sudden cardiac death in these patients.